Short Communication Potentials of Euphorbia tricucalii and Ricinus communis Products for the Control of Callosobruchus maculatus - Kayode, Joshua; Oyeyemi, Sunday (Biological Sciences - PJSIR, 2006)
This study examined the pesticidal effects of seed oil, seed kernel and wood ash extracts from Euphorbia tricucalii and Ricinus communis on cowpea weevil (Callosobruchus maculatus). All the extracts brought about significant reductions in the number of this pest, through contact killing, when compared to the control. The proportion of the pest killed was directly proportional to the concentrations of the extracts, though mortality at the varying extract concentrations was not significantly different from one another. Also, percentage mortality at corresponding extract concentrations from the two botanicals were not significantly different from one another in the three extract products. The trend of the effectiveness of the extracts from the two botanicals tends to suggest that extracts from Ricinus communis were more effective because of their instantaneous reactions on this pest